2013
DOI: 10.1111/ajag.12039
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and risk factors for psychological distress in older men and women affected by the Wenchuan, China earthquake

Abstract: Health-care providers should develop gender-based strategies to improve mental health among older survivors in a long-term post-disaster recovery programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 24 publications
0
14
1
Order By: Relevance
“…For example, more than 40% of working-age women and men experienced psychological distress in the first year following the GEJE, 27,32 and it has been shown that relocation is a risk factor of psychological distress. 27,29 The differences between the present study and previous studies suggest that residents who stay in their own community during the midterm recovery period may have a specific type of resilience. Additionally, a young age in males and health complaints in both genders can be risk factors for psychological distress at 6 to 11 months after a natural disaster 27 ; these findings are consistent with the present results.…”
Section: Discussioncontrasting
confidence: 84%
“…For example, more than 40% of working-age women and men experienced psychological distress in the first year following the GEJE, 27,32 and it has been shown that relocation is a risk factor of psychological distress. 27,29 The differences between the present study and previous studies suggest that residents who stay in their own community during the midterm recovery period may have a specific type of resilience. Additionally, a young age in males and health complaints in both genders can be risk factors for psychological distress at 6 to 11 months after a natural disaster 27 ; these findings are consistent with the present results.…”
Section: Discussioncontrasting
confidence: 84%
“…[ 24 , 26 33 , 35 39 , 41 46 , 48 , 49 , 52 – 54 , 56 – 59 ]. Twenty-one studies reported on populations affected by natural disasters, [ 25 29 , 31 34 , 36 , 39 , 41 , 42 , 44 , 48 , 53 , 54 , 56 – 59 ] 14 by armed conflict, [ 24 , 30 , 35 , 37 , 38 , 40 , 43 , 45 47 , 49 – 52 ], and one for both crisis types [ 55 ]. The definition of older age ranged from ≥45 to ≥65 years of age, with most studies defining it as aged ≥60 years.…”
Section: Resultsmentioning
confidence: 99%
“…The definition of older age ranged from ≥45 to ≥65 years of age, with most studies defining it as aged ≥60 years. The majority of studies were conducted in Asia (China, [ 29 , 33 , 39 , 42 , 54 , 56 – 59 ], India, [ 28 , 53 ] Sri Lanka, [ 34 , 44 ] Pakistan [ 31 , 32 ], and Thailand [ 48 ]), followed by the Middle East (Lebanon [ 30 , 37 , 50 – 52 ] and Iran [ 25 27 ]), sub-Saharan Africa (the Democratic Republic of Congo, [ 24 , 43 ] Ethiopia, [ 35 ] Tanzania, [ 45 47 ] and Mozambique [ 49 ]), Europe (Croatia, [ 38 ] Armenia, [ 36 ] Georgia [ 40 ]), and Latin America (Honduras [ 41 ]), and one study covered 21 countries [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations